Resentimentas kaip atminties funkcija: Nietzsche, Deleuze'as, Jankelevitchius. - Andrijauskas, Jokūbas (Problems / Problemos, 2020)
The aim of this paper is to discuss the later development of Nietzsche's notion of ressentiment in the philosophies of Gilles Deleuze and Vladimir Jankelevitch. In the context of Nietzsche's philosophy, the concept of ressentiment is used to explain a revolution in morality. It is argued that ressentiment should not be understood with appeal to the motivation of a subject, whose notion Nietzsche refuses, or to the intensity of exterior excitation, but rather to the function of memory. In Deleuze's theory, ressentiment is understood as the product of reactive forces that triumph over the active by eliminating the faculty of forgetting. The man of ressentiment is said to be unable to get rid of external excitations and, in turn, he projects his frustration on other people. Because of this, the figure of a "faulty other" functions as a priori of the man of ressentiment. In the philosophy of Jankelevitch, ressentiment is also understood as a negative, anti-vital phenomenon. However, Jankelevitch also introduces the positive notion of ressentiment, which functions as a precondition of authentic forgiveness.